Investigating Direct Links between Depression, Emotional Control, and Physical Punishment with Adolescent Drive for Thinness and Bulimic Behaviors, Including Possible Moderation by the Serotonin Transporter 5-HTTLPR Polymorphism - Rozenblat, Vanja; Ryan, Joanne; Wertheim, Eleanor H.; King, Ross; Olsson, Craig A.; Krug, Isabel (Frontiers in Psychology, 2017)
Objectives: To examine the relationship between psychological and social factors (depression, emotional control, sexual abuse, and parental physical punishment) and adolescent Drive for Thinness and Bulimic behaviours in a large community sample, and to investigate possible genetic moderation. Method: Data were drawn from the Australian Temperament Project (ATP), a population-based cohort study that has followed a representative sample of 2443 participants from infancy to adulthood across 16 waves since 1983. A subsample of 650 participants (50.2% female) of Caucasian descent who provided DNA were genotyped for a serotonin transporter promoter polymorphism (5-HTTLPR). Adolescent disordered eating attitudes and behaviours were assessed using the Bulimia and Drive for Thinness scales of the Eating Disorder Inventory-2 (15-16 years). Depression and emotional control were examined at the same age using the Short Mood and Feelings Questionnaire, and an ATP-devised measure of emotional control. History of sexual abuse and physical punishment were assessed retrospectively (23-24 years) in a subsample of 467 of those providing DNA. Results: EDI-2 scores were associated with depression, emotional control, and retrospectively-reported parental physical punishment. Although there was statistically significant moderation of the relationship between parental physical punishment and bulimic behaviours by 5-HTTLPR (p = .0048), genotypes in this subsample were not in Hardy-Weinberg Equilibrium. No other GxE interactions were significant. Conclusion: Findings from this study affirm the central importance of psychosocial processes in disordered eating patterns in adolescence. Evidence of moderation by 5-HTTLPR was not conclusive; however, genetic moderation observed in a subsample not in Hardy-Weinberg Equilibrium warrants further investigation.